Perception of Bangka Belitung Citizen About Primate Conservation Effort - Dalimunthe, Nurzaidah Putri; Priyansah, Sujadi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The primate species of Bangka Belitung such as Mentilin are categorized as endangered species and are constantly under threat as a result of poaching and habitat destruction. Various conservation efforts have been carried out, one of which is by touching the aspect of public education. However, there has been no specific research on the community's response to primate conservation in Bangka Island. This study aimed to determine the level of public knowledge of primates typical of Bangka Belitung and to determine public perceptions of conservation efforts for primates typical of Bangka Belitung. The research method was carried out by surveying respondents from five different villages in Bangka Island, namely Zed Village, Kemuja, Payabenua, Petaling and Terak Village. The questionnaire consists of three main aspects, namely knowledge, perception and concern for the conservation of primates. In general, the response of the people of Bangka Island to the topic of primate conservation, both in terms of knowledge, perception were relatively low. However, as this was a preliminary study, it is important to explore the reasons behind the responses given in this survey. This will certainly be very useful to be taken into consideration for the primate conservation program that will be carried out by related parties.